Optimization of Online Marketing Strategies in The Middle of The Covid-19 Pandemic in Improving MSME’s Sales - Beta Nur Hidayah; Rif'atus Sholikah; Galuh Setyowati Dwi Safitri; Shofiatur Rochmah; Muhammad Baihaqi Ferdiansyah; Nanik Kustiningsih (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Marketing strategies during the Covid-19 pandemic became a challenge or problem for micro, small and medium enterprises that caused a decline in sales levels, which is our basis for conducting this research. This study aims to increase sales returns by using online marketing strategies amid the Covid-19 pandemic. This study uses a descriptive method with a qualitative approach. Data collection techniques used in this study were observation, interviews, and documentation. Omahadiahsby utilizes social media for online marketing strategies. The social media platforms used by Omahadiahsby to increase its sales include Instagram, Whatsapp, Facebook, Twitter, and Tiktok. The results of this study indicate that the online marketing strategy amid the Covid-19 pandemic carried out by Omahadiahsby is considered very effective and efficient, this is evidenced by an increase in the number of sales in June-October 2020, which is Rp. 31,375,000, - compared to the strategy of Marketing that still uses the offline sales method in January-May 2020 is only Rp. 23,250,000,-. Researchers suggest that micro, small and medium enterprises in Omahadiahsby use online marketing strategies during the Covid-19 pandemic and beyond to increase the number of sales. Not only that